Soil Microbial Community Structure Shifts Induced by Biochar and Biochar‐Based Fertilizer Amendment to Karst Calcareous Soil. Issue 2 (28th March 2019) - Zhou, Zhidong; Gao, Ting; Van Zwieten, Lukas; Zhu, Qian; Yan, Taotao; Xue, Jianhui; Wu, Yongbo
Abstract : Core Ideas: Biochar‐based fertilizer treatments induced significant microbial community structure shifts compared with no‐biochar and biochar alone. Biochar‐based fertilizer especially at higher biochar addition rate increased soil microbial biomass and fertility. Soil microbial species were strongly correlated with soil nutrients under biochar and biochar‐based fertilizer into karst soil. Karst ecosystems are vulnerable to degradation and constitute a significant proportion of southwestern China. Here, we explore the amendment of these soils with wood biochar in combination with N‐P‐K fertilizer and swine manure compost with the goal of improving microbial community structure and soil nutrient status of these soils. A pot experiment with six treatments, including control (CK, no amendment), swine manure compost plus N‐P‐K fertilizer (MF), wood biochar at 2% in soil (W2), wood biochar at 4% in soil (W4), wood biochar‐based fertilizer at 2% in soil (W2MF), and biochar‐based fertilizer at 4% in soil (W4MF), was set up for 20 months. The results showed that soil organic matter and soil available nutrients N, P, and K in W4MF increased by 63.95, 66.23, 284.96, and 94.56%, respectively, compared with CK. Soil microbial biomass C, N, and P increased in sequence by 60.05, 87.64, and 307.85%, respectively. Soil bacterial and fungal diversity indices (Simpson and Shannon) and richness index (Chao1) were generally higher in biochar‐based fertilizer treatments (W2MF and W4MF) than biochar alone (W2 and W4). The bacterial and fungal community structures of biochar based fertilizer treatments differed from those of biochar amendment alone or control ( P < 0.05). Linear discriminant (Effect Size) analysis showed that the bacterial biomarkers of the W2MF + W4MF group were mainly the phylum Acidobacteria and class Alphaproteobacteria, and the fungal biomarkers were the phylum Rozellomycota and Glomeromycota . Redundancy analysis revealed strong relationships between microbial community structure and soil organic matter and soil available nutrients N, P, and K ( P < 0.05). In conclusion, either sole biochar or biochar‐based fertilizer amendment improved karst soil nutrient conditions and induced microbial community structural shifts. The performance was better in biochar‐based fertilizer treatment than that in biochar addition alone.